Multiple Pituitary Adenomas: A Systematic Review - Budan, Renata M.; Georgescu, Carmen E. (Frontiers in Endocrinology, 2016)
PubMed, Scopus and Web of Science Core Collection databases were systematically searched for studies reporting synchronous double or multiple pituitary adenomas (MPA), a rare clinical condition, with a vague pathogenesis. Multiple adenomas of the pituitary gland are referred to as morphologically and/or immunocytochemically distinct tumors that are frequently small-sized and hormonally non-functional, to account for the low detection rate. There is no general agreement on how to classify MPA, various criteria such as tumor contiguity, immunoreactivity and clonality analysis are being used. Among the component tumors, prolactin (PRL)-immunopositive adenomas are highly prevalent, albeit mute in the majority of cases. The most frequent clinical presentation of MPA is Cushing’s syndrome, given the fact that in more than 50% of reported cases at least one lesion stains for adrenocorticotrophic hormone (ACTH). Plurihormonal hyperactivity may be diagnosed in a patient with MPA when more than one tumor is clinically active (e.g. ACTH and PRL) or in cases with at least one composite tumor (e.g. GH and PRL), to complicate the clinical scenario. Specific challenges associated with MPA include high surgical failure rates, enforcing second-look surgery in certain cases, and difficult preoperative neuroradiological imaging evaluation, with an overall sensitivity of only 25% for magnetic resonance imaging (MRI) to detect distinct multiple tumors. Alternatively, minor pituitary imaging abnormalities may raise suspicion, as these are not uncommon. Postoperative immunohistochemistry is mandatory and in conjunction to electron microscopy scanning and testing for transcription factors (i.e. Pit-1, T-pit, and SF-1) accurately define and classify the distinct cytodifferentiation of MPA.